Human infection with Hymenolepis diminuta: case report of a child in rural Vietnam - Vu Thi, Lam Binh; Do Trung, Dung; Tran Huy, Tho; Nguyen Le, Van; Nguyen Thi Nhu, Quynh; Do Ngoc, Anh (The Journal of Infection in Developing Countries, 2024)
Introduction: Cases of human infection with Hymenolepis diminuta are very rare, and only a few hundred cases have been described. We report a rare case of H. diminuta infection in a 16-month-old boy living in a rural area of Bac Giang province, Vietnam. Case presentation: The patient was admitted to the hospital with mild diarrhea, abdominal pain, and several tapeworm segments in his stool, and no other symptoms. The worm was identified as H. diminuta by morphological examination of eggs in a concentrated stool specimen and genetic sequencing of the 18S rRNA gene of the worm. The patient was successfully treated with single oral dose of praziquantel, and he fully recovered. Conclusions: This report presents a rare case of human infection with H. diminuta in Vietnam; and contributes to enhancing our understanding of the epidemiology, clinical manifestation, and treatment protocols of human hymenolepiasis.